(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2012)
A total of 41 species of fungi were isolated from seed samples of barley, maize, soybean, and sunflower collected at different locations in Serbia. The majority of detected species occurred on barley (35 of 41 species or 87.8%) comparing to soybean (17 of 41 species or 41.5%), sunflower (16 of 41 species or 39.0%) and maize (15 of 41 species or 36.9%). Species belonging to genera Alternaria, Chaetomium, Epicoccum, Fusarium, Penicillium and Rhizopus were present on seeds of all four plant species. Alternaria species were dominant on soybean, barley and sunflower seeds (85.7%, 84.7% and 76.9%). F. verticillioides and Penicillium spp. were mainly isolated from maize seeds (100 and 92.3% respectively), while other species were isolated up to 38.5% (Chaetomium spp. and Rhizopus spp.). F. graminearum, F. proliferatum, F. poae and F. sporotrichioides were the most common Fusarium species isolated from barley (51.1-93.3%), while on the soybean seeds F. oxysporum (71.4%), F. semitectum (57.1%) and F. sporotrichioides (57.1%) were prevalent. Frequency of Fusarium species on sunflower seeds varied from 7% (F. equiseti, F. graminearum, F. proliferatum and F. subglutinans) to 15.4% (F. verticillioides). Statistically significant negative correlation (r = –0.678*) was determined for the incidence of F. graminearum and Alternaria spp., as well as, Fusarium spp. and Alternaria spp. (r = –0.614*), on barley seeds. The obtained results revealed that seed-borne pathogens were present in most seed samples of important cereals and industrial crops grown under different agroecological conditions in Serbia. Some of the identified fungi are potential producers of mycotoxins, thus their presence is important in terms of reduced food safety for humans and animals. Therefore, an early and accurate diagnosis and pathogen surveillance will provide time for the development and the application of disease strategies.